Constitutional judges’ specialization in jurisdictional guarantees in Ecuador - Tigua Tigua, Raúl Ramiro; Barreiro Cevallos, Laura Esther (Frónesis, 2024)
The work is analyzed from multiple controversies in constitutional jurisdictional causes that awaken in the administrators of justice the need to study and prevent possible administrative and criminal sanctions; The objective is based on analyzing the attributions of the judges of first and second instance, on the constitutional jurisdictional guarantees. The method used is that of synthesis analysis with which it is possible to conclude that it is unavoidable to prioritize the establishment of courts and chambers specialized in Constitutional cases, in such a way as to guarantee legal security, judicial protection and due process constantly violated by the justice operators and that must be amended by the Constitutional Court and that leads to roll back processes and comprehensive reparation to the victims of these constitutional judicial errors.